하나원 입소 북한 이탈주민의 개인적 특성과 건강 신념이 건강 행위에 미치는 영향 - 전정희(Jeung Hee Jeon); 박영숙(Young Suk Park) (지역사회간호학회지, 2012)
Purpose: The purpose of this study is to provide base data for preparing plans that North Korean (NK) Refugees can adjust themselves to our society with a healthy mind after they get over their health problems using the Health Belief Model, knowing the relationship between individual characteristics and health beliefs, and health behavior. Methods: The subjects were 304 NK adult refugees in Hanawon. Data were collected by demographic questionnaire, health behavior scale, self-efficacy scale, perceived benefit scale, perceived barrier scale, perceived seriousness, perceived sensibility, and individual characteristics. Results: The factors influencing the health behavior of NK refugees were perceived benefits, self-efficacy, the period in the third country and experience in being expelled to NK, and these variables were describing 31.4% of the health behaviors of refugees. Conclusion: The perceived benefits and self-efficacy of health belief and specific experiences related to refugee affected NK refugees' health behavior.